Debunking the Public Health Myth: Municipal Politics and Class Conflict During the Galt, Ontario Waterworks Campaigns, 1888-1890 - Hagopian, John (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1997)
This article refutes the assertion that the Galt, Ontario waterworks was built for public health reasons. The two Galt waterworks campaigns (1888 and 1890) are studied in the context of other contemporaneous local events, the most important of which was a moulders' strike in 1889. Popular resistance to businessmen's wants and public support for the striking moulders prompted the formation of a local board of trade and the threat of an industrial exodus from town. The waterworks authorization of 1890 resulted from the victory by businessmen in this overt class stuggle. The development of Galt's waterworks reflected economic and political interests far more than public health concerns. The findings refut McLaughlin, and illustrate a novel connection between urban politics, infrastructure development, labour relations, and industrial capitalism.